REPRESENTASI PEREMPUAN DALAM KOLOM HUMOR SI PALUI DI BANJARMASIN POST - Vidiadari, Irene Santika (Informasi, 2017)
The focus of this paper is the representation of women on Banjarmasin Post's humourcolumn, "Si Palui," whose stories are either about daily lives or domestic issues. On thelatter topic, the theme which regularly appears is marital problems such as poligamy,divorce, and sexuality. On this column, women characters are merely supporting castsand, hence, are subordinated. This research applies the critical language element of themicro level of Norman Fairclough's Critical Discourse Analysis in order to understandthe representation issues through language: semantics, syntax, and lexycon. Th resultshows that the representation of women on Si Palui is categorized into three: as widows,wives, and other kinds of women. The widows are illustrated as having plumpy bodyand always expecting to get married, though the representation emphasizes on the kindof flirtious widows adored by men. The wives are represented as the sexual objects oftheir husband. Meanwhile other kinds of women, such as mother-in-laws, are fussy, andsingle women are agressive.AbstrakTulisan ini berfokus untuk melihat representasi perempuan dalam kolom humorberbahasa Banjar, Si Palui di Banjarmasin Post. Humor Si Palui menceritakan kejadiansehari-hari dan membahas persoalan rumah tangga. Pada cerita Palui yang bertemarumah tangga, beberapa tema yang sering hadir adalah poligami, perceraian, danseksualitas suami istri. Pada kolom Si Palui, tokoh perempuan hadir sebagai figurandan subordinat. Penelitian ini menggunakan elemen critical language dari level mikropada analisis wacana Fariclough untuk membedah persoalan representasi melaluiaspek bahasa: semantik, sintaksis dan leksikon. Hasil penelitian ini menunjukkanbahwa representasi perempuan dalam teks Si Palui terbagi menjadi tiga: sebagai janda,istri, dan status perempuan lain digambarkan berbeda-beda. Tokoh janda digambarkansebagai tokoh yang berbadan montok, manja, dan ingin segera menikah. Tokoh jandayang mendapat penegasan dalam kolom Palui adalah janda kembang yang menjadiidola laki-laki. Tokoh istri digambarkan sebagai objek seksual suaminya. Perempuanlain, seperti mertua, digambarkan cerewet, dan perempuan lajang diceritakan agresif.